(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
International Large-Scale Assessments (ILSAs) like PISA, TIMSS, and PIRLS have shaken up education policy around the world. These global tests don’t just collect data—they set the tone for what’s important in schools. Suddenly, countries aren’t just looking inward; they’re comparing themselves to everyone else. This article digs into how ILSAs drive policy changes, spark curriculum reforms, and shape new ways to hold schools accountable. There are clear upsides—like smarter, data-driven decision making and a bigger focus on what students can actually do, not just what they memorize. But there are also serious worries: teachers end up teaching to the test, some subjects get squeezed out, and blindly copying “best practices” from top-ranking countries rarely works as planned.